Volume 4A: Combustion, Fuels and Emissions 2015
DOI: 10.1115/gt2015-42536
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Stable Flame Behaviour of Heavy Duty Gas Turbine Burner: RANS, LES and Experiment Comparison

Abstract: VeLoNOx™ series (Very Low NOx) burners have been developed by Ansaldo Energia to satisfy the most restrictive emissions limits required by various countries. For these combustion systems the characterization of the field of stable operating conditions is a key design element. In particular, flame transition is of paramount importance for the stability of these combustion systems. Usually, this phenomenon occurs during load ramps and is characterized by a change of the flame shape, occurring in a well-defined l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The FDF can predict the existence of oscillations of the two modes independently, but will fail in predicting their stability, as the latter is connected to the nonlinear coupling between the two modes. This phenomenon is usually called mode-switching, and was observed also by Moeck and Paschereit [21] and in gas turbines experiments by Cazalens et al [22] and Anisimov et al [23] . In [21] it was shown that mode-switching can be attributed to the existence of an unstable quasiperiodic attractor in the phase-space of thermoacoustic trajectories, which the FDF framework cannot calculate.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The FDF can predict the existence of oscillations of the two modes independently, but will fail in predicting their stability, as the latter is connected to the nonlinear coupling between the two modes. This phenomenon is usually called mode-switching, and was observed also by Moeck and Paschereit [21] and in gas turbines experiments by Cazalens et al [22] and Anisimov et al [23] . In [21] it was shown that mode-switching can be attributed to the existence of an unstable quasiperiodic attractor in the phase-space of thermoacoustic trajectories, which the FDF framework cannot calculate.…”
Section: Introductionmentioning
confidence: 83%
“…For a fixed point, both amplitudes vanish and J simply contains the growth rates σ 1 and σ 2 on the main diagonal, retrieving the classic linear stability result. For a limit cycle solution (say of mode 1), the Jacobian takes the form (23) and has eigenvalues ∂ σ 1 /∂ A 1 A 1 and σ 2 . Because A 1 is positive, the stability is determined by the sign of ∂ σ 1 / ∂ A 1 (the FDF condition) and σ 2 .…”
Section: Stability Criterionmentioning
confidence: 99%
“…With the continuous advancement of advanced, efficient, and clean gas turbine combustion technologies [8], coupled with increasingly stringent emission regulations [9,10], the development of the gas turbine encounters new challenges and demands, including the imperative to simultaneously achieve for higher efficiency, lower NO x and CO emissions, greater fuel flexibility, and a larger operation window [11,12]. The wider operation window is characterized by lower park loads [13], indicating the operational state of the gas turbine at lower loads, and higher ramp gradients, denoting a greater rate of change when adjusting the load, which showcases the greater flexibility and adaptability of gas turbines various operational conditions [14][15][16]. Specifically, increasing the equivalence ratio to enhance combustion is very effective in extending the operation window.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the trails of the pilot flame in the left image are open, whereas they are closed and slightly rolled around the chamber centerline in the right image. Rofi et al [16,38] employed both experiments and Reynolds Averaged Navier-Stokes (RANS) simulations to explore the flame shape before and after flame transition in a single burner combustion chamber developed by Ansaldo Energia. Their findings revealed distinctive flame shape transitions during load ramps, providing valuable insights into the dynamics of combustion stability and emission characteristics of their gas turbine combustor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation